Sevoflurane-Induced Apoptosis in the Mouse Cerebral Cortex Follows Similar Characteristics of Physiological Apoptosis - Wang, Qi; Li, Yuan; Tan, Hong; Wang, Yingwei (Frontiers in Molecular Neuroscience, 2022)
General anesthetics are capable of inducing neuronal apoptosis during the rapid synaptogenesis of immature mammalian brains. In this vulnerable time window, physiological apoptosis also occurs to eliminate excess and inappropriately integrated neurons. We previously showed that physiological and ketamine-induced apoptosis in mouse primary somatosensory cortex (S1) followed similar developmental patterns. However, since sevoflurane is more widely used in pediatric anesthesia, and targets mainly on different receptors, as compared with ketamine, it is important to determine whether sevoflurane-induced apoptosis also follows similar developmental patterns as physiological apoptosis or not. Mice at postnatal days 5 (P5) and P9 were anesthetized with 1.5% sevoflurane for 4 h, and the apoptotic neurons in S1 were quantitated by immunohistochemistry. The results showed that sevoflurane raised the levels of apoptosis in S1 without interfering with the developmental patterns of physiological apoptosis. The cells more vulnerable to both physiological and sevoflurane-induced apoptosis shifted from layer V pyramidal neurons at P5 to layers II–IV GABAergic neurons by P9. The magnitude of both sevoflurane-induced and physiological apoptosis was more attenuated at P9 than P5. To determine whether the Akt-FoxO1-PUMA pathway contributes to the developmental decrease in magnitude of both physiological and sevoflurane-induced apoptosis, Western blot was used to measure the levels of related proteins in S1 of P5 and P9 mice. We observed higer levels of antiapoptotic phosphorylated Akt (p-Akt) and phosphorylated FoxO1 (p-FoxO1), and lower levels of the downstream proapoptotic factor PUMA in control and anesthetized mice at P9 than P5. In addition, the Akt-FoxO1-PUMA pathway may also be responsible for sevoflurane-induced apoptosis. Together, these results suggest that magnitude, lamination pattern and cell-type specificity to sevoflurane-induced apoptosis are age-dependent and follow physiological apoptosis pattern. Moreover, The Akt-FoxO1-PUMA pathway may mediate the developmental decreases in magnitude of both physiological and sevoflurane-induced apoptosis in neonatal mouse S1.